The effect of sandblasting duration on the bond durability of dual-cure adhesive cement to CAD/CAM resin restoratives - Tekçe, Neslihan (J Adv Prosthodont, 2018)
PURPOSE: To evaluate the effect of prolonged sandblasting on the bond durability of dual-cure adhesive resin cement to computer-aided design and computer-aided manufacturing (CAD/CAM) restoratives. MATERIALS AND METHODS: Nano-ceramic LAVA Ultimate and hybrid-ceramic VITA Enamic CAD/CAM blocks were used for this study. Each CAD/CAM block was sectioned into slabs of 4-mm thickness for the microtensile test (µTBS) test and 2-mm thickness for the surface roughness test. Three groups were created according to the sandblasting protocols; group 1: specimens were sandblasted for 15 seconds, group 2: specimens were sandblasted for 30 seconds, and group 3: specimens were sandblasted for 60 seconds. After sandblasting, all specimens were luted using RelyX Ultimate Clicker. Half the specimens were subjected to µTBS tests at 24 hours, and the other half were subjected to tests after 5000 thermocycles. Additionally, a total of 96 CAD/CAM block sections were prepared for surface roughness tests and scanning electron microscopy (SEM) evaluations. The Mann-Whitney U test, Kruskal-Wallis one-way analysis of variance, and Dunn's post hoc test were used to compare continuous variables among the groups. RESULTS: At baseline, group 1, group 2, and group 3 exhibited statistically similar µTBS results for LAVA. However, group 3 had significantly lower µTBS values than groups 1 and 2 for VITA. After 5000 thermocycles, µTBS values significantly decreased for each block (P<.05). CONCLUSION: It is important to perform controlled sandblasting because it may affect bond strength results. Sixty seconds of sandblasting disturbs the initial µTBS values and the stability of adhesion of CAD/CAM restoratives to dual-cure adhesive resin cement for VITA Enamic.